Optimization of coconut milk kefir beverage by RSM and screening of its metabolites and peptides - Taleb Abadl, Muna Mahmood; Marzlan, Anis Asyila; Sulaiman, Rabiha; Abas, Faridah; Meor Hussin, Anis Shobirin (Multidisciplinary Digital Publishing Institute, 2023)
Probiotic foods such as kefir drinks help improve consumers' health and well-being. Since Salmonella resistance to current antibiotic drugs is rising at an alarming rate worldwide, especially in Africa and Asia, this has raised the need for alternative ways of preventing and treating infectious diseases in humans and animals. Thus, a dairy-free probiotic drink can be an alternative for people with milk allergies or those who try dairy products as a lifestyle choice. This study aims to optimize the quality of the coconut milk kefir drink for its antioxidant and anti-microbial activities and to identify the peptides and metabolites present. The time, temperature, and inoculum size, which resulted in the optimal antioxidant and antimicrobial activities using Response Surface Methodology (RSM), were found to be 13.4 h, 25 °C, and 5.4 g/100 mL, respectively. The metabolic changes of coconut milk kefir at the beginning and end of fermentation were identified using 1H-NMR-based metabolomics. Some identified metabolites are γ-Aminobutyric acid, Biotin, Riboflavin, Butyrate, Lactate, Caprylate, and 11 peptide sequences identified using LC-MS/MS. The findings of this study demonstrated a high potential for coconut milk fermented using kefir grains as a functionally healthy drink.